1985
DOI: 10.1128/iai.49.1.164-171.1985
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of plasmid DNA sequences involved in invasion of HeLa cells by Shigella flexneri

Abstract: A large plasmid is found in virulent isolates of Shigella sp. and encodes functions essential for invasion of mammalian cells. To identify plasmid sequences necessary for invasion, we isolated a series of Tn5 insertions in pWR100, the virulence plasmid of Shigella flexneri serotype 5. These insertions demonstrated that three separate EcoRI fragments of pWRlO0 were required for invasion of HeLa cells. However, the corresponding native EcoRI fragments, when cloned into pBR325, did not restore virulence to plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
1
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(149 citation statements)
references
References 26 publications
5
142
1
1
Order By: Relevance
“…Effectors encoded by theTTSS of Shigella are required both for the process of invasion and vacuole lysis (Maurelli et al, 1985;Page et al, 1999;Schuch et al, 1999). We thus wondered whether it was invasion or vacuole lysis step in which the TTSS activation was required for acquiring the G3CS.…”
Section: G3cs Are Recruited During Vacuole Lysis In J774 Macrophagesmentioning
confidence: 99%
“…Effectors encoded by theTTSS of Shigella are required both for the process of invasion and vacuole lysis (Maurelli et al, 1985;Page et al, 1999;Schuch et al, 1999). We thus wondered whether it was invasion or vacuole lysis step in which the TTSS activation was required for acquiring the G3CS.…”
Section: G3cs Are Recruited During Vacuole Lysis In J774 Macrophagesmentioning
confidence: 99%
“…Overlapping cosmids representing the entire virulence plasmid previously were constructed by inserting 40 kb fragments of pWR100 into the vector pJB8 (Maurelli et al, 1985).…”
Section: Construction Of Plasmids and Strainsmentioning
confidence: 99%
“…Genes involved in both steps are carried on a 200 kb virulence plasmid (reviewed by Hale, 1991;Parsot, 1994). A 31 kb fragment of this plasmid is necessary and apparently sufficient for entry into epithelial cells (Maurelli et al, 1985;Sasakawa et al, 1988). This fragment is organized in two divergently transcribed regions which schematically encode secreted proteins, the IpaA-D proteins and a type III secretion system, the Mxi-Spa secretion apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Formal and Dennis Kopecko in the Walter Reed Army Institute of Research in Washington, DC, that identified the virulence plasmid as responsible for host cell invasion capacity, the distinguishing pathogenic property of Shigella (Sansonetti, Kopecko, & Formal, 1981;Sansonetti, D'Hauteville, Formal, & Toucas, 1982;Sansonetti, Kopecko, & Formal, 1982;Sansonetti et al, 1983). Sansonetti et al proceeded to characterise key regions of this plasmid that harboured genes encoding invasion capability, secreted effectors, and a unique cell-to-cell spread phenotype that utilised polymerisation of host cell actin (Baudry, Maurelli, Clerc, Sadoff, & Sansonetti, 1987;Bernardini, Mounier, D'Hauteville, Coquis-Rondon, & Sansonetti, 1989;Hale, Sansonetti, Schad, Austin, & Formal, 1983;Maurelli, Baudry, D'Hauteville, Hale, & Sansonetti, 1985).…”
Section: Shigellamentioning
confidence: 99%